Wood Vinegar as a Complex Growth Regulator Promotes the Growth, Yield, and Quality of Rapeseed - Kunmiao Zhu; Sicheng Gu; Jiahuan Liu; Tao Luo; Zaid Khan; Kangkang Zhang; Liyong Hu (Agronomy, 2021)
Wood vinegar is formed by the condensation of smoke produced during the production of biochar. It mainly contains acetic acid, butyric acid, catechol, and phenol. Wood vinegar has a compound effect of promoting crop growth similar to plant growth regulators and is environmentally friendly. Moreover, it can enhance the biological and abiotic resistance of crops. In this study, foliar spraying was carried out systematically in the field with the hybrid variety of Huayouza 9 for two years to study the effects of wood vinegar and its compounds on the growth of rapeseed (Brassica napus L.). We applied four treatments with tap water as a control (CK), namely wood vinegar diluted 400-fold (M), M mixed with gibberellin (T1), M mixed with sodium D-gluconate (T2), and M mixed with melatonin (T3). They were sprayed in the seedling stage and overwintering stage, respectively. The results showed that the seed yield, the leaf area index, and the number of pods per plant of rapeseed treated with M increased by an average of 9.58%, 23.45%, and 23.80% in two years as compared to the CK, respectively. Compared with M, the seed yield of rapeseed treated with T1, T2, and T3 increased by an average of 7.88%, 6.90%, and 1.32% in two years, respectively. The treatments also improved the quality of rapeseed. In particular, the glucosinolate content of rapeseed treated with T2 and T3 decreased by an average of 12.83% and 6.72% in two years compared to the CK, respectively. The four treatments selected in the current study improved the resistance of rapeseed at the low temperature of 2–6 °C by increasing the activity of superoxide dismutase and proline and soluble protein contents, as compared to the CK. Besides, all treatments containing M reduced the incidence of Sclerotinia sclerotiorum and Peronospora parasitica (downy mildew) in rapeseed. More specifically, the T3 treatment significantly decreased the infection rate of these two diseases mentioned above by an average of 17.33% and 12.14% in two years compared to the CK, respectively. Therefore, the study and application of wood vinegar due to its compound effects on crop growth and yield is of great importance to sustainable agriculture, crop ecology, and environmental protection.